Barriers to career progression faced by women: evidence from a Malaysian multinational oil company - Ismail, Maimunah; Ibrahim, Mariani (Emerald Group Publishing, 2008)
Purpose: This paper seeks to investigate barriers faced by women in acquiring higher positions in a Malaysian multinational oil company. Design/methodology/approach: Data were obtained through a survey involving 78 executive women in the Malaysian oil company. A structured questionnaire was used to gather data. The study used gender role theory, which argues that women are viewed and treated unfavourably when they do not act according to their expected gender roles. Findings: Shows family structure and women's commitment to the family are the most significant barriers perceived by the executive women. This research reveals that women in various job positions do not differ in their perceptions with regard to barriers they face for career progression. Research limitations/implications: The study was conducted among executive women in one company only, hence it cannot be generalized to other oil companies in Malaysia. Practical implications: Provides evidence on family‐, organizational‐ and societal‐related barriers to career progression. The organization should aware of these barriers as they will affect women's professional development. Originality/value: This is a first study of this nature conducted in a large oil company which focuses on women‘s barriers to career progression.